Determiation of Genetic Diversity and Relationhips among Thai Litchi Accessions by RAPD and AFLP Markers - Panie Tongpamnak; Asalaha Patanatara; Peerasak Srinives; Chalongchai Babprasert (Agriculture and Natural Resources, 2002)
Genetic diversity and relationships within Thai litchi cultivars were investigated using RAPD (random amplified polymorphic DNA) and AFLP (amplified fragment length polymorphism) markers. Fourteen RAPD primers and seven AFLP primers were chosen, resulting in amplification of 52 and 101 reproducible polymorphic fragment products, respectively. The percentages of polymorphic markers for RAPD and AFLP were 34.6% and 36.3% respectively. Each marker system was able to differentiate all accessions. Even each of the AFLP primers could identify all accessions, while the RAPD markers did not show such efficiency. The polymorphism information content (PIC) scores were calculated for each of 52 RAPD and 101 AFLP polymorphic fragments. It ranged between 0.16 to 0.50 for RAPD markers and 0.22 to 0.50 for AFLP markers. Unweighted pair-group method with arithmetic averages (UPGMA) dendrograms using Jaccards coefficients reflected no clear cut grouping based on neither morphology nor climatic adaptation. However, both dendrograms showed that the 47 litchi accessions could be classified into groups between when the similarity coefficients were as low as 0.37 for RAPD marker and 0.25 for AFLP markers. Two accessions (LH80 and LH109) were found to be genetically very far distant from the other accessions using both markers. RAPD and AFLP marker analyses provided a quick and reliable alternative for identification of litchi accessions and determination of genetic diversity among them.